2015
DOI: 10.1139/cjpp-2014-0353
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid: molecular mechanisms and therapeutic potential in diabetes

Abstract: Diabetes is a chronic metabolic disease with a high prevalence worldwide. Diabetes and insulin resistance are associated with the development of cardiovascular and nervous diseases. The development of these disorders reflects complex pathological processes in which the oxidative stress caused by reactive oxygen species (ROS) and reactive nitrogen species (RNS) plays a pivotal role. It is widely accepted that diabetes impairs endothelial nitric oxide synthase (eNOS) activity and increases the production of ROS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
135
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(155 citation statements)
references
References 58 publications
(60 reference statements)
2
135
0
13
Order By: Relevance
“…It has been largely reported that diabetes impairs endothelial nitric oxide synthase (eNOS) activity, thus increasing ROS production, with a consequent reduction of NO bioavailability. α-lipoic acid has shown beneficial effects both in the prevention and in the treatment of diabetes because of its insulin-mimetic and anti-inflammatory action; it is also involved in mitochondrial bioenergetic reactions [11]. The positive effects of α-lipoic acid on oxidative stress parameters have been shown by our study: α-lipoic acid increased SOD, an enzyme with the role of commuting highly reactive O 2− into H 2 O 2 , which is subsequently reduced in H 2 O by mitochondrial glutathione peroxidase and catalase [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been largely reported that diabetes impairs endothelial nitric oxide synthase (eNOS) activity, thus increasing ROS production, with a consequent reduction of NO bioavailability. α-lipoic acid has shown beneficial effects both in the prevention and in the treatment of diabetes because of its insulin-mimetic and anti-inflammatory action; it is also involved in mitochondrial bioenergetic reactions [11]. The positive effects of α-lipoic acid on oxidative stress parameters have been shown by our study: α-lipoic acid increased SOD, an enzyme with the role of commuting highly reactive O 2− into H 2 O 2 , which is subsequently reduced in H 2 O by mitochondrial glutathione peroxidase and catalase [12].…”
Section: Discussionmentioning
confidence: 99%
“…[Stacpoole, 2012]. ALA is present in almost all foodtypes [Li, 2015] and although it is readily digested, absorbed, and transported to tissues, including the brain [Carlson et al, 2007;Papanas and Ziegler, 2015;Rochette et al, 2015], the amounts available from diet are low [Li, 2015;D€ orsam and Fahrer, 2016]. In most prokaryotic and eukaryotic microorganisms, plant and animal mitochondria, and plant plastids, ALA is enzymatically synthesized endogenously from octanoate [Spalding et al, 2010;Pashaj et al, 2015;Zhang et al, 2015].…”
Section: Mitochondria and Alzheimer Diseasementioning
confidence: 99%
“…It exists in water soluble oxidized and reduced forms [1]. As an antioxidant, the beneficial effects of LA have been shown on three fronts: (1) scavenging free radicals and reactive oxygen species; (2) chelating metal ions; (3) the regeneration of other antioxidants, such as vitamin E, vitamin C and glutathione [2], which have applications in the prevention and treatment of diabetes (including chronic complications), cerebral and neuro-degenerative diseases, radiation injury, ischemia reperfusion injury, and AIDS [36]. Furthermore, it has recently been reported that LA alone or in combination with paclitaxel can inhibit NF-κB expression and thus, inhibit breast cancer cell proliferation [7].…”
Section: Introductionmentioning
confidence: 99%